MENINGKATKAN KREATIVITAS ANAK USIA 5-6 TAHUN MELALUI MEDIA BAHAN BEKAS - Nila Septianingsih; Luluk Asmawati; Tri Sayekti (Jurnal Penelitian dan Pengembangan Pendidikan Anak Usia Dini, 2017)
This research is motivated by the low creativity of children aged 5-6 years in PAUD DARU AL-AZKIA Pandeglang Banten.. Learning in schools focuses on the worksheet so that the stimulation of children’s creativity is low. The method used in this research is the method of action research with the kemmis and taggart model consisting of planning, action and concurrent implementation and the last reflection. Sources of data in this study amounted to 23 children. The results showed that with the media used materials can improve the creativity of children, it is seen from the average creativity in pre-study of 39.58% experienced an increase in cycle I of 53.52% while the second cycle of 71.68%.